RELATIONSHIP BETWEEN ACTIVE COPING WITH PARENTING STRESS IN MOTHER OF MENTALLY RETARDED CHILD - Umi Mawardah; Siswati Siswati; Farida Hidayati (Faculty of Psychology, Diponegoro University, 2012)
This research was conducted to examine the relationship between active coping with parenting stress in mothers of children mental.Subjek retardation in this study are 66 people who had a mother whose son was mentally retarded child at school SLB ABC Swadaya Kendal. Methods of data collection in this study using two scales, namely Active Coping Scale and Parenting Stress Scale.Simple regression analysis showed an association between active coping with parenting stress in mothers of children with mental retardation. This is shown by the value of 0.756 RY12 with sig (2-tailed) = 0.000 (p <0.05) positive sign on the correlation coefficient indicates the direction of positive relationships. This means that the higher the higher active coping parenting stress, where as the lower active coping, the lower parenting stress. Active coping effectively contributed 57.1% to the stress of caregiving. These results indicate that there is another factor at 42.9%, which also contributed to Parenting Stress is not revealed in this study.